The Relationship of Learning Motivation, Reward and Achievement in Science of Secondary Students in The District of Botolan - Tolero, Josue Alburo; Echaure, Jessie S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
ABSTRACT The study aimed to determine the effect of learning motivation and reward to the achievement in Science among junior high school students of Botolan District, Division of Zambales during SY 2018-2019. The study revealed that the respondent is a typical female. The respondents “strongly agree” on extrinsic, intrinsic and task value while “agree” on views about learning, self-efficacy and belief of achievement as dimensions of learning motivation. The respondents “agree” on tangible and intangible as dimensions on rewards system. The respondents “strongly agree” on indicators towards reward system. The students obtain a “passed” rating in their academic performance. There is no significant difference on the dimensions of learning motivation. There is no significant difference on the dimensions of reward system. There is no significant difference on the dimensions of reward system when grouped according to sex profile variable. There is no significant relationship between the academic performance and the dimensions on learning motivation. The summary of the researches conducted and the assumptions arrived at, the researcher have to give tangible or intangible rewards to deserving students who are exerting efforts to excel in the science class that there is a necessity to train teachers in how to impart students so that they develop intrinsically motivated, as a substitute of just driven along by the idea of the next external reward; that the teachers are to exercise extreme fairness and equality to give rewards and recognition to deserving students.